Two Number Addition Using Drinking Straws and Number Bags in the First Grade of MI Muhammadiyah Pondok Karanganom Klaten - Aulia Nur Handayani; Fitri Yuliawati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aimed to determine the application and improvement of learning outcomes by drinking straws and bag numbers in learning the addition of two numbers. This research was a classroomaction research conducted in class I B of MI Muhammadiyah Pondok Academic Year 2018/2019,totaling 25 students. This research was conducted in 2 cycles consisting of four stages, namelyplanning, action, observation, and reflection. This study used drinking straws and bag numbers aslearning media. The instruments used in this study were RPP, LKPD, guidelines for observationand interviews and documentation. The indicator of the success of this study was in terms of theprocess of teacher and student abilities observed aspects of 80% or 7 of the 8 aspects and in terms ofresults of 80% or 20 of the 25 class, I B students completed the passing grade, which was 65. The results showed that drinking straws and number bags were able to facilitate students in learning the two numbers addition material and were able to improve student learning outcomes, indicatedby learning outcomes that reached KKM in cycles I and II were 68% and 84%. The application ofdrinking straws and number bags could improve the learning outcomes of class I B students at MIMuhammadiyah Pondok Karanganom Klaten.